A META-ANALYSIS: THE UTILIZATION OF NEGATIVE PRESSURE WOUND THERAPY IN DIABETIC FOOT ULCERS - Sanjiwani, Ni Putu Gita Raditya; Murti, I Putu Krisna (Jurnal Rekonstruksi dan Estetik, 2023)
Highlight : Diabetes mellitus has a global prevalence of more than 500 million individuals, and it is associated with a significant consequence known as diabetic foot ulcers (DFUs). Diabetic foot is a commonly observed complication of diabetes mellitus, characterized by the development of non-healing ulcers, which can have a substantial negative impact on the overall well-being of those affected. Negative pressure wound therapy (NPWT) effectively eliminates necrotic tissue and wound secretions, stimulates the production of granulation tissue, mitigates bacterial infection, and expedites the process of wound healing. Abstract: Introduction: Diabetes mellitus has a global prevalence and significant consequence known as diabetic foot ulcers. Negative pressure wound therapy (NPWT) is a modern therapeutic strategy for managing diabetic foot ulcers. The primary objective of this study is to assess the efficacy and safety by doing a thorough literature review and performing a meta-analysis. Methods: The search platforms chosen for this study were PubMed, Embase, and Cochrane Library databases with years of publication between 2013 and 2022. The analysis was conducted using the software RevMan 5.4 and R statistical software. Results: In the present investigation, a total of 291 articles were first subjected to screening. The analysis ultimately included nine relevant literatures after the screening process. The selected literature encompassed a collective sample size of 890 patients. The random effect model used in the analysis revealed a statistically significant discrepancy in the healing rate that had negative pressure wound therapy (NPWT) intervention with the healing rate analysis shows OR 0.77 [0.65, 0.90] p=0.0, and other outcome analysis shows no statistically significant result, adverse event incident OR  0.01 CI [0.00 to 0.04), p =0.23, and amputation rate was OR 0.01 CI [0.00 to 0.02] p = 0.81. Conclusions: This research has provided evidence of the effectiveness of negative pressure wound therapy (NPWT) as a potential approach for accelerating the wound healing process. However, when utilizing this innovative approach, it is imperative to guarantee meticulous regulation and modification of the negative pressure value to mitigate any potential risk of bleeding in the wound.